Nilai Tukar Petani Padi Sawah Di Kecamatan Passi Timur Kabupaten Bolaang Mongondow - Momongan, Janet Deakeni; Waney, Nordy F.L.; Rumagit, Grace A.J. (Sam Ratulangi University, 2024)
This study aims to determine the exchange rate of farmers in Passi Timur Sub-district, Bolaang Mongondow Regency. The research took place from August to October 2023. The research was conducted in Passi Timur Subdistrict, Bolaang Mongondow Regency. The data used in this study consisted of primary data and secondary data. Primary data is data obtained through direct interviews with respondents with a list of questions that have been prepared. Secondary data is data obtained through institutions, agencies, or offices related to this research such as data from the village head office, sub-district office, central statistics agency and so on. Sampling in the study using purporsive sampling method and the sample was 15 respondents of paddy rice farmers in Manembo Village, Poopo Village, and Pangian Village in Passi Timur Sub-district. The data analysis method used in this study uses the analysis of the exchange rate of wet-rice farmers by calculating the exchange rate of farmers (NTP) using the income concept formula. The results showed that the exchange rate of wet-rice farmers in Passi Timur Subdistrict, Bolaang Mongondow Regency obtained through the calculation of farmers' income and expenses amounted to 111.14, which means that wet-rice farmers in Passi Timur Subdistrict are able to meet the daily needs of their families from the results of wet-rice farming.